Penyuluhan Hukum Yang Dilakukan Notaris Kepada Para Pihak Dalam Perspektif Kepastian Hukum - Prakoso, Bhim; Permana, Bayu Indra; Al Farizy, Mohammad Rafi (Acta Comitas : Jurnal Hukum Kenotariatan, 2024)
The purpose of writing this article is to find out the meaning of the Notary's obligations in providing legal education to parties so that they are able to understand what their rights and obligations are when the deed has been signed perfectly and are able to minimize the occurrence of conflicts between the parties making the agreement. The research method used is normative legal research using a statutory approach and a conceptual approach. The research results show that Notaries have the authority to provide legal counseling to parties regarding the preparation of deeds, especially those related to agreements. The urgency of providing legal counseling by a notary to the parties is an obligation to provide legal knowledge to the parties in order to create legal order in society. the emergence of disputes involving the parties and the notary.